Microsatellite Identification Based on Genome Assembly Reveals Potentials Marker of Macassar Ebony (Diospyros celebica Bakh.) - Majiidu, Muhammad; Matra, Deden Derajat; Dwiyanti, Fifi Gus; Siregar, Iskandar Z (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Macassar ebony (Diospyros celebica Bakh.) is an endemic tree species native to Sulawesi. To date, there are limited comprehensive publications regarding its genome assembly. In this study, we employed paired-end libraries of HiSeq 4000 Illumina, generating 141.2 million paired-end reads (42.4 Gigabases). Our analysis revealed the presence of 950,081 Scaffolds, with an N50 value of 6,023. Notably, BUSCO analysis identified 183 (12.7%) complete and single-copy BUSCOs (S), as well as 9 (0.6%) complete and duplicated BUSCOs (D). Furthermore, we identified 12,890 microsatellites within the Macassar Ebony genome. These microsatellites encompass 14 dinucleotide SSR motifs, 12,090 trinucleotide SSRs, 780 tetranucleotide SSR motifs, and 6 pentanucleotide SSRs. This dataset represents a valuable resource for assessing Macassar Ebony genetic makeup in its natural habitats and for subsequent analyses of the Macassar Ebony genome.